Assessing the social and economic implications on water security in the Nelson Mandela Bay Metropolitan Municipality, Eastern Cape of South Africa - Richard Kwame Adom; Mulala Danny Simatele; Memory Reid (IWA Publishing, 2023)
Access to water is a universal human right for every individual and a key instrument in meeting the United Nations' sustainable development goal SDG 6, namely, to ensure safe drinking water and sanitation for all by 2030. Water is also intrinsically linked to any society or country's social, economic and political development. Nevertheless, many communities and households, predominantly rural and underprivileged in the Nelson Mandela Metropolitan Municipality, continue to experience persistent water shortages. This means entrenched poverty, ill health, hunger, stress, and social and economic challenges for the population. Using data collection tools inspired by traditional methods of qualitative and quantitative approaches, this paper scrutinised the social and economic factors contributing to severe inequality in water access in the municipality. Our findings established that water shortage is portrayed as a stand-alone issue without linking it to social and economic challenges. Furthermore, both government and municipalities fail to contextualise a multidimensional problem-solving approach to the water provision challenges in the municipality. This paper, therefore, recommends a multidimensional approach to tackling the problem of accessibility, taking into consideration the social and economic needs of the population. HIGHLIGHTS This paper highlights the inequalities of water provision in Nelson Mandela Metropolitan Municipality.; While some households enjoy uninterrupted access to a reliable water supply, other marginalised communities face regular water shortages or lack access altogether.; The uneven distribution of water resources exacerbates social and economic inequalities within the municipality.;